Variasi Morfologi dan Deteksi Leucocytozoon caulleryi dengan Metode PCR pada Ayam Ras di Wilayah Endemis Indonesia - Endang Suprihati; Wiwik Misaco Yuniarti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
The purpose of this study was to analyze the variation in morphology and detection Leucocytozoon caulleryi by PCR in mtDNA genes cty b that attacking bred chickens in endemic areas of Indonesia. This study was divided into three stages, data collection of Leucocytozoonosis cases in endemic areas of Indonesia; identification of parasites Leucocytozoon caulleryi morphologically through microscopic examination; and the identification of Leucocytozoon caulleryi cyt b genes that attack bred chickens in endemic areas by PCR. The results showed that there are variations in morphology of Leucocytozoon caulleryi that attacking chicken in endemic areas of Indonesia. Gamete morphometry of L. caulleryi had an average length and width 18.233 ± 4.672 dan 12.934 ± 3.349 µm. Nested PCR clearly showed positive reaction of Leucocytozoon infections by amplicons in 600 bp and 03 bp length.